Trabajo para se editado en la revista - Vélez Jiménez, Cristina Elizabeth (2014)
The aim of this work was to study the techno-functional characteristics of by-products from key limes (Citrus aurantifolia Swingle) ) (albedo + residues flavedo, flavedo and worn out pulp); It was worked with a particle size of ≤ 500μm. For determining the water retention capacity (WRC) and the swelling capacity (SW) Robertson et al method was used. (2000), for oil retention capacity (ORC) was taken in consideration Femenia et al. (1997) with some modifications. Fractions lime by-products showed a WRC comprised between 5,14 g water/g dried sample for unwashed flavedo and 8,27 g water/g dry sample flavedo albedo + remains unwashed. The SW was 4,15 mL/g dry sample in flavedo unwashed and 9,69 mL/g dry sample remains in flavedo + albedo wash. The ORC indicated values between 1,95 g/g dry pulp sample drained oil and 2,77 g/g dry sample for washing flavedo. The water retention capacity was influenced by the IDF / SDF ratio and content of IDF, being lower in those fractions with minor level of IDF; confirming the assertions by some authors. The flavedo unwashed and exhausted unwashed pulp showed the lowest values of the properties of hydration.